Application of industrial amylolytic yeast strains for the production of bioethanol from broken rice. (December 2019) - Myburgh, Marthinus W.; Cripwell, Rosemary A.; Favaro, Lorenzo; van Zyl, Willem H.
Graphical abstract: Highlights: Recombinant enzymes sufficiently hydrolyse raw broken rice. Best performing strain reached 100% carbon conversion and theoretical yield in CBP. Complete reduction (100%) in enzyme loading achieved by best performing strain. Fully capable CBP yeast for ethanol production from broken rice substrate. Abstract: Amylolytic Saccharomyces cerevisiae derivatives of Ethanol Red™ Version 1 (ER T12) and M2n (M2n T1) were assessed through enzyme assays, hydrolysis trials, electron microscopy and fermentation studies using broken rice. The heterologous enzymes hydrolysed broken rice at a similar rate compared to commercial granular starch-hydrolysing enzyme cocktail. During the fermentation of 20% dw/v broken rice, the amylolytic strains converted rice starch to ethanol in a single step and yielded high ethanol titers. The best-performing strain (ER T12) produced 93% of the theoretical ethanol yield after 96 h of consolidated bioprocessing (CBP) fermentation at 32 °C. Furthermore, the addition of commercial enzyme cocktail (10% of the recommended dosage) in combination with ER T12 did not significantly improve the maximum ethanol concentration, confirming the superior ability of ER T12 to hydrolyse raw starch. The ER T12 strain was therefore identified as an ideal candidate for the CBP of starch-rich waste streams.